PEMBELAJARAN THINK PAIR SHARE UNTUK MENINGKATKAN PENGUASAAN KOMPUTER PROGRAM MICROSOFT WORD - Triyanto, (Pendidikan Dasar, 2010)
Abstract; The purposes of this action research are: 1) describing the implementation of think pair share technique in the teaching and learning Microsoft word program, 2) describing the process of increasing the ability of learning the program, 3) describing how think pair share learning model is implemented to increase the ability of deaf students of grade VII/C in learning such a program. Having one cycle consisting of three meetings, the finding shows that the model is quite effective to increase the student ability to learn Microsoft word program.